Didactic games for rockline teaching in Civil Engineering (Research, Society and Development, 2020)
The use of games and simulations is an alternative method of teaching that can make learning more effective through the relationship between knowledge and practice, without the risks of failure of real situations. Games and simulations can also be used as training aid instruments in order to form the necessary skills where current knowledge is not sufficient. In this sense, this work aims to discuss the use of the Lego System game® for the teaching of the balance line technique for engineering students, used in the discipline of planning and costs of the postgraduate course in civil engineering at the Federal University of Ceará. For this purpose, a simulation of planning the construction of houses with games was carried out: it consisted of the construction of a set of four houses. Concepts such as service scheduling with intense planning phase, pallet system for materials, durations of activities, organization of the shop floor (layout of the construction site), standardization of services, use of transport kambans and production were used. It was found that the use of games for teaching work programming with balance line facilitates the understanding of theoretical concepts and their practical application.